Perancangan Website Penjualan Kerajinan Kulit Pada Roosman Leather And Natural Handicraft - Khultsum, Umi; Sardiarinto, Sardiarinto (IJNS - Indonesian Journal on Networking and Security, 2020)
ABSTRACT-Many people get information about company products from the internet or from sales websites. Especially at this time all community activities are supported by internet media, so to find and get information more easily. Not only large companies are interested in using the website as a sales medium, but also small and medium-sized companies, because it can have a big impact by increasing the number of products sold. Roosman leather craftsmen already have a website that is a company profile website, but the website cannot be used to make transactions. The transaction process is still done directly in the store. The sales mechanism that still uses the conventional system is less effective in terms of time and cost. Then information about the product on the website is still lacking. Customers often run out of stock models of some existing products because the website used does not provide information about the availability of product stock. In this case it is not uncommon for customers to cancel the purchase. If this happens sustainably then the income of Roosman leather craftsmen will decrease. Therefore a sales website was made with the construction of this system using the waterfall model method. With the establishment of the sales website, customers can carry out transactions without having to come to the store and make it easier to find information about superior products. Keywords: website, sales, leather craft ABSTRAK-Banyak masyarakat memperoleh informasi mengenai produk-produk perusahaan dari internet atau dari website penjualan. Terutama saat ini segala kegiatan masyarakat didukung dengan media internet, jadi untuk mencari dan mendapatkan informasi lebih mudah. Tidak hanya perusahaan-perusahaan besar yang tertarik menggunakan website sebagai media penjualan tetapi juga perusahan kecil dan menengah, karena dapat memberikan dampak yang besar yaitu meningkatkan jumlah produk yang terjual. Pengrajin kulit Roosman sudah mempunyai website yaitu website company profil, namun website tersebut tidak dapat digunakan untuk melakukan transaksi. Proses transaksi masih dilakukan secara langsung di toko. Mekanisme penjualan yang masih menggunakan sistem konvensional tersebut kurang efektif dari segi waktu dan biaya. Kemudian informasi mengenai produk di website tersebut masih kurang. Pelanggan seringkali kehabisan stok model dari beberapa produk yang ada dikarenakan website yang digunakan tidak memberikan informasi mengenai ketersediaan stok produk. Dalam hal ini tidak jarang pelanggan membatalkan pembelian tersebut. Apabila hal tersebut terjadi secara berkelanjutan maka pendapatan pada pengrajin kulit Roosman akan mengalami penurunan. Maka dari itu dibuatlah website penjualan dengan pembangunan sistem ini menggunakan metode model waterfall. Dengan Terbentuknya website penjualan tersebut maka pelanggan dapat melalukan transaksi tanpa harus datang ke toko dan memudahkan dalam mencari informasi mengenai produk-produk unggulan. Kata Kunci : website, penjualan, kerajinan kulit